Benefits and Challenges of AI-Based Digital Twin Integration in the Saudi Arabian Construction Industry: A Correspondence Analysis (CA) Approach - Aljawharah A. Alnaser; Haytham Elmousalami (Applied Sciences)
The Fourth Industrial Revolution (4IR) has accelerated the construction industry’s shift toward digital transformation. This progress is mainly driven by the emergence of innovative technologies, including artificial intelligence (AI) and digital twins (DTs). While global research has extensively explored the benefits and challenges of AI-based DTs, the rapid growth of Saudi Arabia’s construction sector—fueled by substantial local investments and international partnerships—underscores the urgent need to examine their specific impact within this context. To address this gap, this study aims to investigate the potential benefits and challenges of integrating AI-driven DTs into Saudi Arabia’s construction industry. To achieve this, a structured literature review and a survey were conducted among architecture, engineering, and construction (AEC) firms, with 106 complete responses analyzed using correspondence analysis (CA). The findings revealed that AI-driven DTs substantially benefit Saudi Arabia’s construction industry. For example, among the 17 identified benefits, the top-ranked ones include AI capabilities to improve analytics, AI’s facilitation of digital twins in modeling complex real-world systems, and the facilitation of strategic decision making. However, several challenges hinder the realization of these benefits, including a lack of standardization of integrated DT and AI in construction projects, a lack of understanding of AI’s capabilities, a lack of logistics and the limited availability of IT infrastructure, and the complexity of AI algorithms. These findings underscore the transformative potential of integrating AI-driven DTs to optimize construction performance, improve decision-making, and address real-world complexities. This study provides actionable insights for stakeholders and recommends future research exploring strategies for overcoming adoption challenges, fostering technological innovation, and capacity building in Saudi Arabia’s construction sector.